Neutrophil and lymphocyte locomotion in patients with selective IgA deficiency - Coşkun, Yavuz; Sanal, Özden; Ersoy, Fügen (The Turkish Journal of Pediatrics, 1990)
Neutrophil chemotaxis was studied in 14 patients, twelve with selective and two with partial IgA deficiency. Twelve of the 14 patients were also evaluated for lymphocyte locomotion. Zymosan activated serum was used to stimulate cell migration, and Boyden chambers were used for both neutrophil and lymphocyte chemotaxis assays. Evaluation of the results of neutrophil and lymphocyte locomotion showed that chemotaxis to ZAS, random migration and chemotactic index values were not significantly different when comparing the patients with the controls.